PENGARUH PROFITABILITAS, LEVERAGE DAN UKURAN PERUSAHAAN PADA NILAI PERUSAHAAN MELALUI PENGUNGKAPAN TANGGUNG JAWAB SOSIAL - Armadi, I Wayan; Astika, Ida Bagus Putra (E-Jurnal Akuntansi, 2016)
Each investor in deciding to invest in the capital market requires information about the company's financial reports such as profitability, leverage, company size, corporate social responsibility and corporate value. This is because the implementation of CSR is able to affect the company's performance. This reasearchin on companies on the Stock Exchange period 2011-2013. Samples were taken deliberately so as much as 17 used as a sample. With a simple linear regression analysis obtained results of this study as follows, CSR disclosured significant impact on the return on assets (ROA) and the cumulative abnormal return (CAR). It means that CSR disclosure by the company will provide a positive and significant effects on the company's financial performances & the performance enterprise market. This means that with the penggungkapan CSR company, then chances, trespon positively by investors and many investors who invest in the company that led to the increased performance of the company.
Keywords: BEI, CSR, and profitability